Rivers [electronic resource] - Burnham, Laurie; Nash, Geoffrey H. (New York : Chelsea House, 2007)
Presents an introduction to rivers, describing how they were formed and how they have changed over time, and provides the history and description of ten of the world's most famous rivers
1. Origin of the landform: Rivers -- 2. Nile, Africa -- 3. Amazon, South America -- 4. Yangtze, Asia -- 5. Mississippi, North America -- 6. Huang Ho, Asia -- 7. Yenisey, Asia -- 8. Ob', Asia -- 9. Congo River, Africa -- 10. Amur River, Asia -- 11. Mackenzie River, North America
Description based on print version record
Includes bibliographical references and index
Keywords: Rivers